Peran Strategi Digital Marketing dan Laporan Keuangan dalam Keberlanjutan Bisnis Kopi Bhumi Kalegan - Nur Rohma Puspitasari; Ika Wulandari (Bengkulu Institute, 2025)
This community service activity aims to improve the sustainability of Kopi Bhumi Kalegan's business through the implementation of digital marketing strategies and the improvement of more structured financial statements. The implementation is carried out through three stages, namely needs analysis through interviews with business owners, program implementation in the form of collaboration in the creation of digital promotional content and the arrangement of a financial recording system based on Google Sheets, as well as evaluation of marketing effectiveness and the regularity of financial statements. The results of the activity show that the use of digital marketing is able to expand the reach of promotions, increase consumer engagement, and attract new customers through consistent visual content. Meanwhile, improvements in financial records produce more accurate and easy-to-analyze financial information, making it easier for business owners to make strategic decisions. The integration between digital marketing and organized financial recording has been proven to improve the professionalism of business management and support business sustainability in the midst of increasingly competitive competition in the coffee industry, This activity concludes that technology optimization and strengthening financial literacy can have a real impact on the development of small businesses such as Bhumi Kalegan Coffee.